Consultation with Teachers : VPF on Acknowledgement within PBIS - Frei, Robin (My University, 2012)
This study examined the effects of Visual-Performance Feedback (VPF) by collecting permanent product data from the acknowledgement portion of Positive Behavior Interventions and Supports (PBIS) and providing teachers with individual feedback on their rates of acknowledgement. Past studies have examined increasing specific, contingent, praise to students and found it an effective intervention for increasing student positive behaviors and decreasing negative behaviors for individual students, small groups, and classroom-wide (Conroy et al, 2009; Gable et al, 2009; Mesa, 2005; Partin et al, 2010). Visual-Performance feedback on teachers intervention implementation has been shown to support change and monitor treatment integrity (Greshham, 1989; Reinke et al, 2007; Wilkinson, 2006).
Color poster with text, graphs, and images.
Keywords: Teacher-student relationships; Classroom management; Behavior modification; Positive Behavior Interventions and Supports; Visual-Performance Feedback; Posters